Understanding Users in the 'Field' of Medications - Peri J. Ballantyne (MDPI AG, 2016)
The numbers of medicinal drugs available for human consumption have increased rapidly in the past several decades, and physician prescribing practices reflect the growing reliance on medicines in health care. However, the nature of medicines-as-technology makes problematic taken-for-granted relationships among actors involved in the delivery, or who are the recipients of medicines-reliant health care. In this article, I situate the medicine user in the 'field' of medications-where interests, actions and outcomes are continually negotiated among and between the various players-physicians, pharmacists, government regulatory bodies, the pharmaceutical industry and users of medicines. The objective of the paper is to illuminate the complex context in which the medicine-user-the target of the pharmacy profession's service to the public-accesses and uses medicines.